The Opportunities for Expanding the Production of Food and Fodder Grain in the Context of Food Security of the Republic of Armenia - Aleksanyan, Vardan; Hovhannisyan , Davit; Matinyan , Alvard; Ghukasyan , Abraham (Bulletin of Yerevan University G: Economics, 2022)
The production of grain has strategic importance from the point of view of ensuring the food security and national security of the Republic of Armenia, therefore, the problems of its production have always been in the center of attention of state.The article analyzes the development trends of animal husbandry in 2005–2021 which provides more than 50% of the gross agricultural output of the RA, the state of feed production, the predominance of combined feed in the feed ration and the issues of formation of a grain-oriented animal husbandry management system.Agriculture is facing two important problems: to expand its own production of food and fodder grain. In this dilemma, food grain should have priority, as only 10% of the total demand is used as intended. However, should not be ignored the need to expand fodder grain production, as it is an important factor in the production of livestock products.The article suggests to revise the provisions of the agrarian policy and to develop a set of tools through which it would be possible to promote the production of grain. In particular, it was suggested to establish a mandatory state order for grain for agricultural farms, as well as to review direct subsidy structures to protect producers from price fluctuations and ensure their stable incomes.
Keywords: livestock breeding; food security; fodder and food grain; agrarian policy; promotion of grain production; grain Committee; quota